Identification of small molecules that disrupt vacuolar function in the pathogen Candida albicans. - Helene Tournu; Jennifer Carroll; Brian Latimer; Ana-Maria Dragoi; Samantha Dykes; James Cardelli; Tracy L Peters; Karen E Eberle; Glen E Palmer (PLoS ONE)
The fungal vacuole is a large acidified organelle that performs a variety of cellular functions. At least a sub-set of these functions are crucial for pathogenic species of fungi, such as Candida albicans, to survive within and invade mammalian tissue as mutants with severe defects in vacuolar biogenesis are avirulent. We therefore sought to identify chemical probes that disrupt the normal function and/or integrity of the fungal vacuole to provide tools for the functional analysis of this organelle as well as potential experimental therapeutics. A convenient indicator of vacuolar integrity based upon the intracellular accumulation of an endogenously produced pigment was adapted to identify Vacuole Disrupting chemical Agents (VDAs). Several chemical libraries were screened and a set of 29 compounds demonstrated to reproducibly cause loss of pigmentation, including 9 azole antifungals, a statin and 3 NSAIDs. Quantitative analysis of vacuolar morphology revealed that (excluding the azoles) a sub-set of 14 VDAs significantly alter vacuolar number, size and/or shape. Many C. albicans mutants with impaired vacuolar function are deficient in the formation of hyphal elements, a process essential for its pathogenicity. Accordingly, all 14 VDAs negatively impact C. albicans hyphal morphogenesis. Fungal selectivity was observed for approximately half of the VDA compounds identified, since they did not alter the morphology of the equivalent mammalian organelle, the lysosome. Collectively, these compounds comprise of a new collection of chemical probes that directly or indirectly perturb normal vacuolar function in C. albicans.